In vivo skin moisturizing measurement by high‐resolution 3 Tesla magnetic resonance imaging. Issue 3 (27th October 2016) - Mesrar, J.; Ognard, J.; Garetier, M.; Chechin, D.; Misery, L.; Ben Salem, D.
Abstract : Background: Magnetic resonance imaging (MRI) is rarely used for the exploration of skin, even if studies have validated both feasibility of skin MRI and its interest for anatomical, physiological, and biochemical study of the skin. The purpose of this study is to explore moisturizing of the different skin layers using 3‐T scan. Methods: An MRI of the heel's skin was performed using a 23 mm coil diameter on a 3T scan with a FFE (Fast Field Echo) 3D T1‐weighted sequence and a TSE (Turbo Spin Echo) calculation T2‐weighted sequence (pixels size of respectively 60 and 70 μm). This study was conducted on 35 healthy volunteers, who were scanned before applying moisturizer topic and 1 h after applying it. Region of interest in the stratum corneum, the epidermis and the dermis were generated on the T2 mapping. The thickness of each layer was measured. The T1 sequence allowed accurate cross‐examination repositioning to ensure the comparability of the measurements. Results: Among the 35 cases, two were excluded from the analysis because of movement artifacts. Measurements before and after moisturizer topic application displayed a T2 increase of 48.94% ( P < 0.0001) in the stratum corneum and of 5.45% ( P < 0.0001) in the epidermis yet without significant difference in the dermis. There was no significant link between the thickness of the stratum corneum and the T2 increase. However, there was a strong correlation between the thickness of the stratum corneum and the thickness of the epidermis ( P < 0.001; rhô=0.72). Conclusion: High‐resolution MRI allows fine exploration of anatomical and physiological properties of the skin and can further be used to extend the studies of skin hydration.